A Case Study on Teacher Educators' Technology Professional Development based on Student Teachers' Perspectives in Malawi. Issue 1 (3rd June 2021) - Gondwe, Foster
Student teachers' perspectives on how their teacher educators act as exemplars of using technology appropriately (or fail to do so) could create a basis for teacher educators' technology professional development (TPD). However, there is a dearth of research on student teachers' input into teacher educators' TPD, as research is dependent on self-reports of teacher educators' own competencies. This study explored teacher educators' TPD based on perspectives of student teachers. The study involved policy analysis, a survey, and interviews with student teachers in a university-based teacher education programme in Malawi. Findings indicate that student teachers have a stake in what it means to be a professional teacher educator in Malawi. The case study has also shown the contribution of student teachers' perspectives in strengthening teacher educators' TPD. The contribution includes clarifying the image of a technologically competent teacher educator and student teachers' co-learning with teacher educators. The paper discusses scholarly and practical implications of these findings. For instance, it is suggested that teacher educators should make the co-learning process more explicit to the student teachers.